Pengaruh Media Animasi Komputer Terhadap Hasil Belajar Siswa Kelas Iv Di Sd Inpres 2 Tondo Pada Mata Pelajaran IPAS - Siti Nur aziza Z.E Ma'lum; Herlina; Rizal; Zulnuraini (JURNAL DIKDAS, 2023)
This research aims to determine whether there is an influence of computer animation media on the learning outcomes of class IV students at SD Inpres 2 Tondo in the science and sciences subject. This research method uses a quasi-experimental research method, the research design uses a Two Group Pretest – Posttest design. For research techniques, random sampling techniques are used. The sample in this study consisted of 39 students from classes IVA and IVB, consisting of 18 students from class IVA as the experimental class and 21 students from class IVB as the control class. The instrument of this research is a learning outcomes test in the form of 15 multiple choice questions. Data were analyzed using SPSS to find out significant achievements between the two groups, the experimental group used computer animation media while the control class used book media. Based on the significant value of the Paired Sample T Test is 0.001, with a significant T-test value <0.05 (0.001 <0.05) and a significance level of 5% (0.05), then Ha is accepted and Ho is rejected. So it can be concluded that there is an influence of computer animation media on the learning outcomes of fourth grade students at SD Inpres 2 Tondo in the science and sciences subject. Computer animation media makes students active in the learning process so that it can improve students' science learning outcomes.